An angiogenic marker for early prediction of preeclampsia - Archana A; Sumitha A; Sathiyapriya V; Ursula Sampson (Asian Journal of Medical Sciences, 2022)
Background: Preeclampsia is a pregnancy-specific disease associated with a high incidence of maternal and fetal morbidity and mortality with classical features of hypertension, proteinuria, and edema. Aims and Objectives: The aims of the study were to study the angiogenic marker for the early predicting of preeclampsia. Materials and Methods: Blood samples were collected from 75 healthy singleton pregnant women from 19 to 29 years between 12 and 16 weeks of gestation with no underlying medical illness. The serum soluble endoglin (sEng) level and serum uric acid levels were estimated. Patients who developed preeclampsia were classified as mild and severe. They were classified as severe preeclampsia if their serum sEng levels are above 8.5 ng/ml and mild preeclampsia was grouped when the serum sEng level varies from 7.1–8.4 ng/ml. The serum sEng and serum uric acid levels were compared. Serum sEng was processed by ELISA technique and serum uric acid was measured by Uricase method in autoanalyzer. Results: The mean uric acid level was 4.0±0.5 mg/dl in severe preeclampsia and 3.6±0.2 mg/dl in mild preeclampsia patients. The levels were within normal limits. The serum sEng levels were 8.7±1.4 ng/ml in severe preeclampsia and 7.7±0.3 ng/ml in mild preeclampsia. The levels are elevated in preeclampsia. Women with serum sEng levels between 7.1 and 8.2 ng/ml developed symptoms of mild preeclampsia between 28 and 30 weeks of gestation, whereas women with serum sEng levels between 8.5 and 13.4 ng/ml developed symptoms of severe preeclampsia between 26 and 28 weeks of gestation. Conclusion: Serum uric acid levels were within normal limits in preeclampsia patients, whereas serum sEng levels were elevated in these patients. Thus, this study concludes that serum sEng will be a good predictor of severity of preeclampsia compared to serum uric acid level.